2009
DOI: 10.1007/s11325-009-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of sleep-disordered breathing symptoms in young and middle-aged Pakistani employed adults

Abstract: The prevalence of SDB symptoms in Pakistani employed adults was comparable to Western populations. However, male gender and smoking were not significant risk factors for SDB symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Adewole and colleagues estimate a 32% habitual snoring prevalence in a small sample of 370 adults in Nigeria (5). In one of the first studies in a Pakistani population, Hussain and colleagues surveyed 2497 adults and reported an average prevalence of self-reported snoring of 32%, yet in middle age (>35 years of age) prevalence was 46% (6). In a sample of 8583 Japanese adults (35-79 years of age) prevalence rates were 24% for men and 10% for women (7).…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Adewole and colleagues estimate a 32% habitual snoring prevalence in a small sample of 370 adults in Nigeria (5). In one of the first studies in a Pakistani population, Hussain and colleagues surveyed 2497 adults and reported an average prevalence of self-reported snoring of 32%, yet in middle age (>35 years of age) prevalence was 46% (6). In a sample of 8583 Japanese adults (35-79 years of age) prevalence rates were 24% for men and 10% for women (7).…”
Section: Prevalencementioning
confidence: 99%
“…Hussain and colleagues distinguished between habitual and occasional snoring (5.4% versus 26.9%) with the former being defined as "daily" (6). Other studies have defined habitual snoring as 4 "often"; or more than 3, 4 or 5 times per week.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…One large (n = 3470) questionnaire based study 13 was done in Pakistan in which Family history of snoring was observed one of significant risk factors (OR 2.9, 2.5-3.5) for OSA symptoms along with age, body mass index, collar size, nasal blockage. OSA is common in patients with craniofacial disorders; however, even in individuals without a specific disorder, alterations in craniofacial structure confer risk for OSA.…”
Section: Original Ar Ticlementioning
confidence: 99%
“…1 The prevalence of snoring in the general population is estimated to exceed 50%. 2,3 Interest in understanding the mechanism and implications of snoring preceded the advent of polysomnography and the characterization of sleep-disordered breathing (SDB). 4 Studies of snoring have often suffered from use of subjective self-report, lack of standardized measurement techniques, and inadequate adjustment for underlying obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%